Concordancia entre el motivo de consulta y el diagnóstico final en pacientes pediátricos - Castaneda Villa, Norma; Ventura Cruz, Doris (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Concordance analysis using Cohen’s Kappa index (k) has been widely used in clinical research to determine the degree of agreement between two measurements made by the same observer (intra-observer agreement) or between the measurements of two observers on the same variable (inter- observer agreement). In this work, we used to determine the degree of inter-observer agreement between the reason for consultation and the final diagnosis issued by an interdisciplinary team of The Mexican Institute of Hearing and Language (IMAL). The institute receives around ten pediatric patients per month; the reasons for consulting these patients are diverse. In this research, 53 pediatric patients completed their studies in the IMAL and received a final diagnostic. A research assistant manually collected the data from the medical records of the IMAL Medical Direction. For example, 1) reason for consultation, 2) studies carried out, 3) recommendations, and 4) the final diagnosis. The global concordance between consultation and the definitive diagnosis was